Ketogenic effects of medium chain triglycerides containing formula and its correlation to breath acetone in healthy volunteers: a randomized, double-blinded, placebo-controlled, single dose-response study - Nakamura, Kentaro; Hagihara, Keisuke; Nagai, Naoko; Egashira, Ryuichiro; Takeuchi, Mariko; Nakano, Mai; Saito, Hitomi; Moriguchi, Misaki; Tonari, Satoko; Fujii, Hisako; Miyake, Akimitsu; Omae, Yusuke; et al. (Frontiers in Nutrition, 2023)
The efficacy of low-carbohydrate, high-fat diets, such as ketogenic diets, for cancer patients is of research interest. We previously demonstrated the efficacy of the ketogenic diet in a case study in which medium-chain triglycerides (MCTs) or MCT-containing formula (ketogenic formula) was used as a supplement to increase blood ketone bodies. However, little is known about the amounts needed to induce ketogenic effects and about the usefulness of monitoring of breath acetone. To investigate the pharmacokinetics of MCTs and their metabolites, blood ketone bodies and breath acetone, 24 healthy subjects received one of four single oral doses of the ketogenic formula (equivalent to 0, 10, 20, and 30 g of MCTs) under fasting conditions. Total blood ketone bodies, β-hydroxybutyrate, octanoic acid, and decanoic acid were increased in a dose-dependent manner. The ketogenic effect was considered to depend on octanoic and decanoic acids, because a positive correlation was observed between them. A strong positive correlation was also observed between total serum ketone bodies and breath acetone at each time points. Therefore, monitoring breath acetone levels seems a less invasive method to predict blood concentrations of ketone bodies during ketogenic diet therapy.